Pengaruh Pelatihan dan Lingkungan Kerja terhadap Kinerja Karyawan PT. Perkebunan Nusantara IV Kebun Adolina Perbaungan - Siregar, Adek Gustina; Iriani, Iriani; Yudha, Tri Kartika (JRMB (Jurnal Riset Manajemen & Bisnis), 2023)
This research aims to determine how much influence training and the work environment partially have on the performance of PT employees. Perkebunan Nusantara IV Taman Adolina Perbaungan. This research method is quantitative and the sample determination in this study used the Slovin formula from 242 respondents to 71 respondents. The data sources use primary data, namely questionnaires, interviews, observations, and secondary data obtained from documentation studies and literature studies. The data analysis technique used is multiple linear regression test, f test, t test, and determination test using SPSS version 22. The results of research using the t statistical test show that the training variable (X1) partially has a positive and significant effect on employee performance (Y), namely the value obtained tcount ttable (4.171 1.667) with a significance level of 0.000 0.05 and the work environment variable (X2) partially has a positive and significant effect on employee performance (Y), obtained by the value tcount ttable (4.078 1.667) with a significance level of 0.000 0.05. The results of the F test on the training variable (X1) and work environment (X2) can be concluded that the training variable (X1) and work environment (X2) simultaneously have a positive and significant effect on employee performance (Y), namely the value obtained Fcount Ftable(143.850 3.22) with a significance level of 0.000 0.05